Number of women on boards of large companies keeps growing: Momentum from inclusion requirement, however, is waning - Anja Kirsch; Virginia Sondergeld; Katharina Wrohlich (DIW Weekly Report, 2023)
The upward trend in women's representation on executive and supervisory boards of major companies in Germany continued in 2022, although the overall momentum has slowed yet again. Growth on executive boards in particular has slowed, as the most recent DIW Berlin Women Executives Barometer shows: Following a significant increase at the 200 largest companies from 2020 to 2021, there was only a one-percentage-point increase to just under 16 percent in the share of women on executive boards in 2022. The greatest increases were in the DAX-40 companies, where there was a share of women on executive boards of over 20 percent for the first time, and companies with government-owned shares, where the share reached 30 percent for the first time. A similar development can be seen in supervisory boards, albeit on a higher level. This development suggests that the companies subject to the inclusion requirement for executive boards, which has been in effect since 2021, implemented it quickly, but have since slowed their efforts. With the Equal Participation of Men and Women in Leadership Positions Act and its successor, policymakers have recently significantly improved the conditions for more women in top bodies. Now companies must do the work, as gender parity remains a distant prospect in many places. Most importantly, companies should make efforts to create an inclusive work culture.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; executive directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executive boards; CEOs; women; finance industry; financial sector; private and public banks; insurance companies